DESAIN DIDAKTIS PADA KONSEP LUAS PERSEGI BERBASIS PERMAINAN DAM-DAMAN DI SEKOLAH DASAR - Khairul Saleh; Mhmd Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to produce a valid, reliable, and practical assessment instrument to measure learning independence in science learning in elementary schools. In this study, learning independence adapted by Widuroyekti which consists of 5 constructs namely free responsibility, progressive thinking, initiative, self-control, and self-establishment. The research method used is development research using the 4-D model. The subject of this research involved 40 respondents from the total number of students in class V of SD Negeri 002 and SD Negeri 011 Pasir Sialang. The data were analyzed using the SPSS version 25.00 for Windows program. The results showed that all questionnaire items were valid and reliable with an average Cronbach Alpha reliability value of (0.893>0.6), and each statement item had a value of (0.797 - 0.867) with a total construct value of 0.832. It can be concluded that the availability of an instrument that is feasible to use to measure student learning independence in science learning in elementary school that meets the requirements as a valid, reliable, and practical test.